2022
DOI: 10.1021/acsami.1c22137
|View full text |Cite
|
Sign up to set email alerts
|

Flory–Huggins VOC Photonics Sensor Made of Cellulose Derivatives

Abstract: As a widespread air pollutant, volatile organic compounds (VOCs) are harmful to the human body's skin, nervous system, and respiratory system. Low-cost, extensive, and continuous detection of VOCs is of great significance to human health. We infiltrated and coated cellulose acetate on the inverse opal photonic crystal skeleton of methylcellulose−polyvinyl alcohol−graphene oxide to construct a degradable, high-toughness cellulose VOC sensor. Cellulose acetate enhances the response to VOCs and achieves a highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…As discussed above, for a solvent analyte, the sensor–analyte interactions mainly depend on the solubility of filler hydrogel in the solvent. Flory–Huggins parameter χ reflects the solubility of polymer in a solvent, while the squared difference of Hildebrand solubility parameter of the polymer and the solvent (Δδ 2 ) indicates the difference of cohesive energy between polymer and solvent. , It is worth noting that the Δδ 2 contains the influence of polarity difference and hydrogen bond interactions between the polymer and solvent. It can be concluded that the key factors for achieving high affinity between the hydrogel based PC sensors and solvent analytes are similar polarity, similar Hildebrand solubility parameter, and a small Flory–Huggins parameter.…”
Section: Recent Progress Of High-sensitivity Colorimetric Pc Sensorsmentioning
confidence: 99%
“…As discussed above, for a solvent analyte, the sensor–analyte interactions mainly depend on the solubility of filler hydrogel in the solvent. Flory–Huggins parameter χ reflects the solubility of polymer in a solvent, while the squared difference of Hildebrand solubility parameter of the polymer and the solvent (Δδ 2 ) indicates the difference of cohesive energy between polymer and solvent. , It is worth noting that the Δδ 2 contains the influence of polarity difference and hydrogen bond interactions between the polymer and solvent. It can be concluded that the key factors for achieving high affinity between the hydrogel based PC sensors and solvent analytes are similar polarity, similar Hildebrand solubility parameter, and a small Flory–Huggins parameter.…”
Section: Recent Progress Of High-sensitivity Colorimetric Pc Sensorsmentioning
confidence: 99%
“…In this regard, Zhang et al proposed a Flory–Huggins VOC photonic sensor based on cellulose derivatives, which offers a new idea for solving the above problems. 73 The combination of PhC cellulose-based sensors has attracted widespread attention in the academic community since they are the most abundant polysaccharides in nature, which has the advantages of low cost and environmental friendliness. By coating cellulose acetate (CA) on the inverse opal PhCs skeleton of methylcellulose–polyvinyl alcohol–graphene oxide (MC-PVA-GO) a degradable and high-toughness cellulose VOC sensor was constructed for selective acetone vapor detection (Fig.…”
Section: Polymersmentioning
confidence: 99%
“…11,12 When the photonic band gap of the PC locates in the visible range, structural color will be generated; and when the refractive index or thickness of the PC changes, the stimulation signal can be transformed into a color variation and a visual detection effect is produced. 13−15 Heretofore, some studies have focused on adding new functional materials to PCs to detect VOCs, such as functional polymers, 16−18 biomass materials, 19 graphene, 20 inorganic materials, 21−23 and metal−organic frameworks (MOFs). 24 Among them, MOFs, which are formed by metals and organic ligands, have been paid much attention due to their adjustable and porous structures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Heretofore, some studies have focused on adding new functional materials to PCs to detect VOCs, such as functional polymers, biomass materials, graphene, inorganic materials, and metal–organic frameworks (MOFs) . Among them, MOFs, which are formed by metals and organic ligands, have been paid much attention due to their adjustable and porous structures. Currently, the sensing detection platform derived from MOFs has gradually entered the public’s vision. However, the MOF-based PC sensors usually show the problems of insufficient color saturation and poor optical conversion performance to realize colorimetric gas sensing.…”
Section: Introductionmentioning
confidence: 99%